Developing Sales Management Information System for UD Niko Semarang Using Midtrans Integration - Caren Lorenza Indra Lesmana; Bernardinus Harnadi; T. Brenda Chandrawati (Journal of Business and Technology, 2026)
UD Niko is still using an outdated operating system which hampers daily operations and increases the error rate. This kind of system is not efficient, as it creates an opportunity for errors and makes it hard to follow the stock. The research problem focuses on the kind of information system to be designed for UD Niko and the features to incorporate, as well as how effective it would be. The study seeks to develop a web-based management information system that supports stock and account receivables management and invoice recording and integrates with Midtrans to facilitate digital payments. The way the system was built is called the waterfall model. The resulting system includes features such as internal stock management, supplier, sales and freelance roles, accounts receivable and payable modules, invoice history and reporting functions, while integrating digital payment via Midtrans. The system testing used the blackbox method and interviews with the owner and employees of UD Niko. The system adequately meets the company’s needs because it enables faster transactions, simplifies record keeping and efficiently manages inventory and reports. Overall, the system improves business management and operational efficiency at UD Niko.